Is the financial market driving income distribution? An analysis of the linkage between income and wealth in Europe - Ilja Kristian Kavonius; Veli-Matti Törmälehto (European Central Bank (ECB), 2022)
Globalisation has a major impact on the levels and distribution of wealth. The financial markets are highly integrated, and valuations of financial assets follow international patterns, which has contributed to large increases in financial wealth over the past 25 years. Nonetheless, this has not led to an equally large increase in property income because the rates of return have decreased during the same era. Moreover, changes in functional income distribution (capital/labour shares) have not been fully transmitted to the distribution of primary income between households because other institutional sectors - particularly the government sector - hold considerable amounts of financial assets. At least in the short term, the decrease in rates of return seems to contradict claims that, due to an increase in both financial and inherited wealth, we are entering an era of increasing income inequality. In this article, the link between financial wealth and pre-tax household income distribution is scrutinised for three European countries using a conceptually fully consistent macro framework. First, national balance sheets are combined with the related income flows. After this, income flows that are not property income but are considered part of national income (e.g., wages and salaries) are added, the national income flows are broken down by institutional sector and the household sector income flows separated. Finally, distributional household micro data are used to break down the aggregate household sector income flows by income decile. The article utilises this framework to analyse the evolution of rates of return and capital and labour shares as well as how the property income flows created by financial wealth have affected household primary income distribution.
Keywords: D10; D31; D32; E21; G51; 330; functional distribution; income distribution; national income; households; wealth